Pentapeptide Protects INS-1 Cells From hIAPP-Mediated Apoptosis by Enhancing Autophagy Through mTOR Pathway - Lin, Jianzhen; Jiao, Ao; Lv, Wu; Zhang, Chengshuo; Shi, Yue; Yang, Zhaoming; Sun, Ning; Li, Xiaohang; Zhang, Jialin (Frontiers in Pharmacology, 2019)
Human islet amyloid polypeptide (hIAPP), the major component of islet amyloid deposition, is one of the amyloidogenic peptides and has been associated with β cell loss and dysfunction in type 2 diabetes (T2D). Autophagy plays a central role in the clearance of hIAPP aggregates, thereby diminishing the hIAPP-induced cytotoxicity. Conversely, hIAPP has been reported to have interfering effects on the autophagy. The pentapeptide FLPNF developed in our previous study has been shown to have effects on the level of the downstream proteins of mTOR and autophagy-lysosome pathway. In the present study, the peptide FLPNF-mediated increase in autophagy flux and its underlying mechanisms, as well as its protecting effect on INS-1 cells, were investigated. Autophagy flux in INS-1 cells overexpressing hIAPP (hIAPP-INS-1 cells) markedly increased after exposure to peptide FLPNF for 24 h and peaked at a concentration of 200 µM. Peptide FLPNF enhanced the autophagy by inhibiting the mTORC1 activity. Flow cytometry results showed the peptide FLPNF bind to mammalian target of rapamycin (mTOR), and further molecular docking analysis revealed a direct interaction between peptide FLPNF and the FRB domain of mTOR. Meanwhile, both peptide FLPNF and rapamycin significantly decreased the hIAPP-induced apoptosis, whereas 3-MA increased the apoptosis. Furthermore, peptide FLPNF reduced the hIAPP oligomer and improved the hIAPP-INS-1 cells insulin release function at high glucose concentration. Taken together, the peptide FLPNF decreased the hIAPP oligomer via upregulating autophagy by inhibiting mTORC1 activity, thus protecting the INS-1 cells from hIAPP-induced apoptosis and improving the insulin release function of INS-1 cells.